2017
DOI: 10.4183/aeb.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Menin in the Human Thyroid Gland

Abstract: Introduction. The expression of menin in the thyroid gland has long been debated. Animal models with targeted inactivation of menin in the thyroid gland have shown that its inactivation might play a role in the progression to a more aggressive type of cancer. Human studies are conflicting, some have identified mutations in the MEN1 gene in a subtype of oncocytic thyroid carcinomas, while others have not identified a higher prevalence of thyroid cancer in MEN1 patients. Objective. To analyze the immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Further molecular studies are needed to evaluate to potential of menin protein in thyroid tumorigenesis and the relationship between these thyroid tumors and MEN1. The expression of menin is generally preserved in human thyroid carcinoma and can be decreased or absent in certain types of thyroid cancer including PTC [11]. The inactivation of menin in the thyroid gland of young mice in uenced the proliferation of follicular cells [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further molecular studies are needed to evaluate to potential of menin protein in thyroid tumorigenesis and the relationship between these thyroid tumors and MEN1. The expression of menin is generally preserved in human thyroid carcinoma and can be decreased or absent in certain types of thyroid cancer including PTC [11]. The inactivation of menin in the thyroid gland of young mice in uenced the proliferation of follicular cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence to exclude the accidental occurrence of MEN1 with PTC in this patient. Based on the current reports of the correlation between the inactive menin status and human thyroid carcinoma, menin can be decreased or absent in certain types of thyroid cancer including PTC [11] and the inactivation of menin in the thyroid gland in uences the proliferation of follicular cells [13], we also supposed that PTC and nodular goiter might be considered as new component of MEN1. However, there is no evidence to con rm it now for the rare incidence.In the future, we hope to summarize the statistical signi cance of PTC and MEN1 as the number of cases reported worldwide increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menin plays an important role in cell division and proliferation, cell cycle regulation and genomic stability. Mutations of MEN1 gene can lead to functional loss of menin, and occurrence of multiple tumors[ 6 - 11 ]. Gene mutation analysis is an important diagnostic method for MEN1[ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that expression of menin is preserved in human normal thyroid tissue and thyroid tumors, but it can be decreased or absent in certain types of thyroid tumors[ 11 - 14 ]. Currently, little is known about the prevalence of papillary thyroid carcinoma (PTC) and nodular goiter in MEN1 patients, and it is unclear whether tumorigenesis of these thyroid tumors is MEN1 related.…”
Section: Introductionmentioning
confidence: 99%